Efficacy of Right-Sided Cervical Sympathetic Block in Treating Post-Traumatic Stress Disorder in Australian Cohorts: A Retrospective Analysis - Paul Verrills; Eugene Lipov; Robert Wright; Zubin Sethi (Research and Practice in Anesthesiology, 2023)
Background: Post-traumatic stress disorder (PTSD) is a prevalent and debilitating condition in Australia. Success rates for current therapies may be delayed and inconsistent. This has led clinicians to explore other options, with cervical sympathetic blockade (CSB) being one of potential promise due to its high efficacy and rapid therapeutic onset. The original paper describing CSB was published in the United States of America (USA), and this was followed by multiple reports of successful PTSD treatment using stellate ganglion block (SGB). To date, no report of CSB utility in Australia has entered the medical literature. Objective: To evaluate the efficacy of CSB as a treatment option for patients diagnosed with PTSD in multiple Australian cohorts. Study Design: Retrospective cohort study. Setting: An established anesthesia pain clinic in 4 Australian cities (Sydney, Brisbane, Perth, Melbourne). Methods: The total cohort included 99 consecutive cases of patients diagnosed with PTSD and treated with right-sided CSB, performed by eight providers across 4 cities (Sydney, Brisbane, Perth, Melbourne). The primary outcome measurement was the PTSD Checklist Score version DSM-5 (PCL-5), which established the initial diagnosis of PTSD. PCL-5 data collection commenced in July 2021 and data regarding trauma specifications was collected beginning in July 2022. Patient demographic and clinical information collected included age, gender, and type of trauma experienced. Results: After the exclusion of cases due to missing data points, 99 patients were included in the final statistical analysis, having completed PCL-5 pre and post-CSB, between 7 and 30-days post-intervention. The patient population included civilian men (n=49) and civilian women (n=50). We identified 22 types of self-reported trauma leading to PTSD. The average decrease in PCL scores for men and women was 23.69 and 21.64, respectively. Statistically significant improvements in PTSD symptoms were noted across varying sources of causative trauma type and gender. Limitations: Limitations include the limited scope of observation giving exclusive focus on pre-and post-PCL data, the limited duration of observation, the self-reported nature of the patient-provided data, and the provision of treatment by eight physicians across multiple locations. Conclusion: CSB seems to be an effective treatment for PTSD symptoms irrespective of gender, trauma type, PTSD-related drug use, suicide attempt, or age, in Australian cohorts.